PEMANFAATAN FUNGI Aspergillus flavus, Aspergillus tereus, DAN Trichoderma harzianum UNTUK MENINGKATKAN PERTUMBUHAN BIBIT Bruguiera cylindrica di DESA NELAYAN INDAH - Ade Khana Saputri; Yunasfi Yunasfi; Mohammad Basyuni (Program studi Kehutanan USU, 2015)
Mangrove forest is one of coastal ecosystems that have high productivity. Recently, mangrove damaged either directly or indirectly. Direct damage for example logging, timber harvesting, settlement construction and ponds manufacturing, ports and roads construction, and arrest biota in mangrove ecosystems. Furthermore, indrectly threat maybe caused by coastal dredging, disposal of waste and industrial waste in the sea and the coast, coastal and marine mining, and deforestation. As a result above-mentioned threat of degraded mangrove forests. Therefore, it is needed for rehabilitation efforts. The research was conducted in September 2014 to January 2015 using a completely randomized design (CRD) with treatments of A. flavus, A. tereus and T. harzianum and with five replications. Results showed that different fungi treatment provided different growth response. The highest mean of height growth obtained from B. cylindrica seedlings treated with A. tereus that was 7.29 cm. The largest diameter was obtained seed treated with T. harzianum by 0.42 cm. The highest value of dry weight obtained from seedlings treated with fungi A. tereus that was 1.74 g. The largest leaf area obtained from seedlings treated with fungus of T. harzianum, that was 402.23 cm2.Keywords: A. flavus, B. cylindrica , fungi, Mangrove, T. harzianum.